Heat transfer enhancement and migration of ferrofluid due to electric force inside a porous medium with complex geometry. (21st August 2019) - Vo, Dat D; Saleem, S; Alderremy, A A; Nguyen, Truong Khang; Nadeem, S; Li, Zhixiong
Abstract: The migration of ferrofluid particles due to an electric field within a porous space is examined. An algorithm was developed for CVFEM to solve the coupled equations. The properties of Fe3 O4 –ethylene glycol nanofluid are dependent on the electric field and on the shape of the nanoparticles. The energy equation seems more interesting in the presence of a radiative term. The influence of nanoparticles' shape, voltage, radiation parameter and Darcy number on nanofluid thermal behavior has been described. Average Nusselt number increases with expansion of the thermal radiation in the system. Enhancing the shape factor causes the Nusselt number to increase. The Darcy number yields more random patterns of isotherms.